CtDNA Predicts Overall Survival in Patients With NSCLC Treated With PD-L1 Blockade or With Chemotherapy. (2021) - Zou, Wei; Yaung, Stephanie J.; Fuhlbrück, Frederike; Ballinger, Marcus; Peters, Eric; Palma, John F.; Shames, David S.; Gandara, David; Jiang, Yuqiu; Patil, Namrata S.
Abstract : PURPOSE: Identification of predictors for overall survival (OS) allows timely detection of clinical efficacy signals and therefore facilitates treatment decisions. We assessed the association between circulating tumor DNA (ctDNA) metrics and the primary end point of OS in a subset of previously treated patients with locally advanced or metastatic non–small-cell lung cancer, who underwent atezolizumab or docetaxel treatment in the open-label randomized phase III OAK trial. MATERIALS AND METHODS: Plasma from 94 patients at baseline and at subsequent cycles of therapy every 3 weeks was analyzed retrospectively for ctDNA. ctDNA was measured by allele frequency and mutant molecules per milliliter (MMPM). Concordance between various per-sample metrics and clinical outcome were assessed using C index. RESULTS: Of all the ctDNA metrics tested, the association of median MMPM at 6 weeks with OS in patients treated with atezolizumab or docetaxel had a C index > 0.7. The OS hazard ratios relative to high ctDNA above median MMPM within each arm were 0.28 (95% CI, 0.11 to 0.75) for atezolizumab and 0.19 (95% CI, 0.08 to 0.48) for docetaxel. For patients who had ctDNA median MMPM levels of < 4.79, the median survival time was more than 17 months in docetaxel-treated patients and the median survival time was not reached in the atezolizumab-treated patients. CONCLUSION: ctDNA MMPM levels measured at 6 weeks post-treatment are associated with OS in advanced non–small-cell lung cancer. Our results suggest that ctDNA has the potential for a noninvasive early liquid biopsy predictor for OS that warrants further studies to demonstrate its utility in clinical development.